Sigmoid isostiffness-lines: An in-vitro model for the assessment of aortic stenosis severity - Buffle, Eric; Stucki, Michael; Zheng, Shaokai; Chiarelli, Maxime; Seiler, Christian; Obrist, Dominik; de Marchi, Stefano F. (Frontiers in Cardiovascular Medicine, 2022)
Background The aortic valve opening area (AVA), used to quantify aortic stenosis severity, depends on the transvalvular flow rate (Q). The currently accepted clinical echocardiographic method assumes a linear relation between AVA and Q. We studied whether a sigmoid model better describes this relation and determined "isostiffness-lines" across a wide flow spectrum, thus allowing building a nomogram for the non-invasive estimation of valve stiffness. Methods Both AVA and instantaneous Q (Qinst) were measured at 10 different mean cardiac outputs of porcine aortic valves mounted in a pulsatile flow loop. The valves' cusps were chemically stiffened to obtain three stiffness grades and the procedure was repeated for each grade. The relative stiffness was defined as the ratio between LV work at grade with added stiffness and at native stiffness grade. AVApeak corresponding to the selected Qpeak of the highest 3 and 5 cardiac output values were predicted in a K-fold cross-validation using sequentially a linear and a sigmoid model. Accuracy of each model was assessed with the Akaike information criterion (AIC). Results The sigmoid model predicted more accurately AVApeak (AIC for prediction of AVA with Qpeak of the 3 highest cardiac output values: -1743 vs -1048; 5 highest cardiac output values: -1471 vs -878) than the linear model. Conclusion This study suggests that the relation between AVA and Q can be better described by a sigmoid than a linear model. This construction of "isostiffness-lines" may be a useful method for the assessment of aortic stenosis in clinical echocardiography.